"Conversations réflexives" dans la classe de langues virtuelle par conférence asynchrone - Marie-Noëlle Lamy; Robin Goodfellow (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
In the UK Open University the principle that distance language learners should be encouraged to reflect on their own learning has traditionally been central to the design of conventional (i.e. print, audio and video) course materials. However, since Computer-Mediated-Communication (CMC) technologies have created the possibility for learners to interact with each other and with teachers and native-speakers - thus providing opportunities for practice and intrinsic feedback on communicative competence - an issue has arisen around the continuing role of conscious reflection. Is it, in fact, still necessary, in a more interactive learning environment? We argue here that it is, and that a challenge faces the developers of the virtual classroom for distance learners in combining the processes of conscious reflection with those of spontaneous interaction. In our view the medium of asynchronous conferencing is particularly well-suited to this as it is flexible with regard to place and pace, and able to support both monologue-like and conversation-like forms of written language exchange. Here we examine some examples of CMC exchanges generated during an Online course in French, and propose a pedagogy which focuses on the generation of what we are calling "reflective conversation", i.e. computer-mediated asynchronous discussion around language topics and language-learning issues.